“And you feel like you’re suffocating … how the fuck am I going to get out of all this?” Drivers and experiences of suicidal ideation in the Australian construction industry - Tyler, Simon; Gunn, Kate; Clifford, Bob; Procter, Nicholas (Frontiers in Psychiatry, 2023)
This research was designed to generate understandings of drivers and experiences of suicidal ideation and distress among Australian Construction Industry (ACI) workers, as well as what helped during experiences. Fifteen participants, from a variety of ACI or closely associated roles, with an average age of 45 years (29 – 66), engaged in individual, semi-structured interviews. Interviews were audio-recorded with consent and analyzed using descriptive thematic analysis. Eight themes relating to what may drive the presence of suicidal ideation and distress were identified; 1) challenges of working within the ACI; 2) relationship and family issues; 3) social disconnection; 4) personal financial hardship; 5) perceived lack of support; 6) alcohol and drug use; 7) child custody/access and legal issues; and 8) experience of mental health challenges, trauma, or a significant adverse life event. Four themes relating to experience and expression of suicidal ideation and distress were identified: 1) suicidal thoughts; 2) impaired thinking; 3) observable expressions of suicidal distress; and 4) lack of observable expressions of suicidal distress. Six themes relating to what helped during experiences and well as what can be done by the ACI to help mitigate experiences, were identified: 1) presence of colleague and managerial support; 2) MATES in Construction; 3) engagement with non-work activities and social support; 4) personal skills and knowledge relating to suicide and mental health; 5) high level industry integration and engagement with support programs; and 6) work hours and expectations changes. Findings highlight several industry and personal related challenges that may drive experiences, with many potentially mitigatable by ACI changes and focused prevention strategies. Participant suicidal thought descriptions align with previously identified constructs deemed central in suicidal trajectories. While findings highlight several observable expressions of suicidal ideation and distress, challenges associated with identifying and assisting individuals in the ACI who may be struggling were also reported. Several factors that helped ACI workers during experiences, as well as what the ACI can do to mitigate future experiences, were identified. Recommendations are made based on these findings, encouraging a more supportive work environment, as well as continued development and increased awareness of support and education systems.